Ambient computing : how invisible hardware, self-starting apps, and nonstop surveillance reshape our public and private lives - Barlow, Mike (Michael Alan) (O'Reilly Media, 2016)
Consider this scenario: You walk into a building and a sensor identifies you through your mobile phone. You then receive a welcoming text telling you when lunch will be served, or perhaps a health warning based on allergy information you've stored in your profile. Maybe you'll be flagged as a security threat. How is that possible? This O'Reilly report explores ambient computing--hands-free, 24/7 wireless connectivity to hardware, data, and IT systems. Enabling that scenario requires a lot of work behind the scenes to determine network connectivity, device security, and personal privacy. With an ambient-computing technology stack already in the works, resolving those issues is only a matter of time. Through interviews with front-line tech pioneers--including Ari Gesher (Kairos Aerospace) and Matthew Gast (Aerohive Networks)--author Mike Barlow explores how real-time analytics can enable real-time decision making. How will simple beacons broadcast information to your phone as you pass businesses on your morning walk? How can emotional speech analysis monitor the emotional state of employees, students, or people in crowds? Pick up this report and find out.